RADIO RIA FM SEBAGAI MEDIA SIAR BAGI KELUARGA DAN KAUM WANITA: Studi Deskriptif Kualitatif Program Siar Pada Radio Ria FM - Kartikasari, Irene; Ramadhian, Ramadhian; Anggitia, Paramastu Titis (JURNAL KOMUNITAS, 2014)
Radio is an auditory medium or media that can only be heard, and can be brought cheap populist or heard anywhere. Radio as a medium has the greatest power of imagination because the media is blind to visualize the voice announcer or factual information through the listener's ear. Broadcasting program is very important for the implementation of a radio broadcast. In this research the authors are using theory by Rhenald Kasali (1999), to be able to know the stage of broadcast program conducted by Ria FM radio. The broadcasting program components include segmentation, targeting, formatting, programming. This research uses descriptive qualitative method, to determine the broadcast program conducted by Ria FM radio with audience segmentation family and women. The research showed that the presence of the broadcast media for women , does not remove the listener from the men who are included in the family . as well as broadcasting programs that support to families , ranging from children to the elderly can all join in a program broadcast on Ria FM radio . The fourth component into the program broadcast on FM radio Ria include stages of segmentation, targeting , formatting , programming . Segmentation is determined through the marketing process , the needs of listeners , and the productive age group that can be heard by anyone . Targeting the show is determined by the content can also be determined through such interactive pathways , sms , facebook , twitter , and through the quiz . Formatting has been determined from the beginning Ria FM joined the production team of Sonora and Ria FM live only running it alone . Programming , ranging from the type of program , program schedules, and its relationship with advertisers all done with the idea of the producer and the other production team .